AKTIVITAS ANTIOKSIDAN EKSTRAK DAUN DAN BATANG KACA PIRING (GARDENIA JASMINOIDES ELLIS) DENGAN METODE DPPH, FRAP DAN CUPRAC - Adriel, Davin
Free radicals are species that have one or more unpaired electrons therefore they can be very reactive. Antioxidants can interact with free radicals and stop the chain reaction. Antioxidant can be found in many plants, including the cape jasmine (Gardenia jasminoides Ellis). Cape jasmine was chosen because its leaves and stems are still rarely used, not like its fruits and flowers which usually processed into essential oil or perfume. Goals of this research were to study antioxidant activity of leaves and stem of cape jasmine by determining IC50 of DPPH (2,2-diphenyl-1-picrylhydrazyl), EC50 of FRAP (Ferric Ion Reducing Antioxidant Power), and EC50 of CUPRAC (Cupric Ion Reducing Antioxidant Capacity); determine total phenolic and flavonoid content; analyze the correlation between total phenolic and flavonoid content with antioxidant activities; correlation between three antioxidant testing methods. Extraction was conducted by reflux method using three solvents with increasing polarity. Determination of total phenolic, flavonoid content, and antioxidant activities were performed by UV- visible spectrophotometry. Correlation between total phenolic and flavonoid content with antioxidant activitites, correlation between three antioxidant testing methods were performed using Pearson’s method. IC50 of DPPH leaves and stem extracts of cape jasmine in the range of 0,31 – 8,44 µg/mL, EC50 of FRAP 39,68 – 183,74 µg/mL, and EC50 of CUPRAC 36,09 – 228,92 µg/mL. The highest total phenolic content (9,71 ± 0,30 g GAE/100 g) and total flavonoid content (and 2,45 ± 0,01 g QE/100 g) was given by ethanolic leaves extract. Total phenolic content in stem extracts gave significantly negative correlation with EC50 of FRAP and EC50 of CUPRAC. Total flavonoid content in stem extract showed significant and negative correlation with IC50 of DPPH. EC50 of FRAP had positive and significant correlation with EC50 of CUPRAC of all sample. All leaves and stem extracts of cape jasmine were categorized as very strong antioxidant by DPPH method. Phenolic compounds in stem extracts had major contribution in antioxidant activities by FRAP and CUPRAC methods. Flavonoid compounds in stem extracts had major contribution in antioxidant activities by DPPH method. FRAP and CUPRAC methods gave linear result in antioxidant actitivites of all sample.